Effect of 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin exposure on acetylcholinesterase during myogenic differentiation of contractile rat primary skeletal muscle cells. (1st August 2019) - Luo, Yali; Xie, Heidi Qunhui; Chen, Yangsheng; Xia, Yingjie; Sha, Rui; Liu, Yiyun; Ma, Yongchao; Xu, Tong; Xu, Li; Wah-Keung Tsim, Karl; Zhao, Bin
Abstract: Emerging data indicate that prenatal exposure to 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD) could interfere with myogenic differentiation in vivo . Acetylcholinesterase (EC3.1.1.7; AChE), an enzyme critical for cholinergic neurotransmission, is abundantly expressed in neurons and mature myotubes, and we recently found that muscle AChE expression was suppressed in parallel with the inhibition of myogenic differentiation upon TCDD treatment in mouse C2C12 cells. This TCDD-induced suppression of muscle AChE was proposed to involve an aryl hydrocarbon receptor (AhR)-independent mechanism, but the precise underlying mechanism remains unclear. Considering the widely recognized role of muscular activity in AChE expression and its potential crosstalk with the AhR signaling pathway, we sought to investigate the effect of TCDD on muscle AChE expression in the presence of muscular activity. Therefore, we employed a highly contractile rat primary skeletal muscle culture system in which AChE activity and the expression of genes related to it (AChE T subunit and collagen Q (ColQ)) were increased during the myogenic differentiation process. Although TCDD treatment successfully induced the expression of genes regulated by AhR activation, the treatment exerted no notable effects on myogenic differentiation. Moreover, muscle AChE enzymatic activity and mRNA level remained unchanged following TCDD treatment, and only ColQ mRNA expression was slightly increased after 4-day treatment with TCDD (10 −10  M). The compensatory role of muscle-contraction-related signaling pathways in this newly identified unresponsiveness of muscle AChE to TCDD warrants further investigation. Highlights: TCDD exerts no effect on the differentiation of contractile rat primary muscle cells. TCDD does not affect AChE expression in contractile primary muscle cells. AhR is functional in contractile primary muscle cells. Muscle contraction might counteract the effect of TCDD treatment.